2015
DOI: 10.1152/ajpgi.00029.2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intestinal barrier function and gut microbiota in high-fat diet-fed rats are dynamic and region dependent

Abstract: Hamilton MK, Boudry G, Lemay DG, Raybould HE. Changes in intestinal barrier function and gut microbiota in high-fat diet-fed rats are dynamic and region dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
210
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(237 citation statements)
references
References 54 publications
16
210
2
9
Order By: Relevance
“…Here, we found that HF diet alters the composition of the fecal and cecal microbiota even after a short-term (30 d) consumption, as previously shown (38,39,43). Moreover, when we specifically analyzed the microbiota associated to the ileal mucosa, we found that HF diet favored emergence of the genus Akkermensia, a finding supported by similar observations in rat models (43,71). Akkermansia members, and more specifically Akkermansia muciniphila, have been identified as mucin-degrading bacteria residing in the mucus layer (72).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Here, we found that HF diet alters the composition of the fecal and cecal microbiota even after a short-term (30 d) consumption, as previously shown (38,39,43). Moreover, when we specifically analyzed the microbiota associated to the ileal mucosa, we found that HF diet favored emergence of the genus Akkermensia, a finding supported by similar observations in rat models (43,71). Akkermansia members, and more specifically Akkermansia muciniphila, have been identified as mucin-degrading bacteria residing in the mucus layer (72).…”
Section: Discussionsupporting
confidence: 86%
“…Studies have shown that, on the basis of long-term administration (9-22 wk), obesogenic diets, such as HF diet, reduce the diversity and richness of the fecal and cecal microbiota (32,68), altering the Firmicutes/Bacteroidetes balance by increasing Firmicutes (Erysipelotrichaceae), Verrucomicrobia, and decreasing Bacteroidales S24-7 (69,70). Here, we found that HF diet alters the composition of the fecal and cecal microbiota even after a short-term (30 d) consumption, as previously shown (38,39,43). Moreover, when we specifically analyzed the microbiota associated to the ileal mucosa, we found that HF diet favored emergence of the genus Akkermensia, a finding supported by similar observations in rat models (43,71).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The microbiota has been found to be required for almost all animal models of obesity (30), and may play a role in the vagal and hypothalamic inflammation that accompanies leptin resistance, hyperphagia and the onset of overweight in susceptible animals (31)(32)(33)(34)(35)(36). Microbial transplants have been shown able to transfer the phenotypes of both overweight and liver pathology / altered blood sugar regulation to lean germ-free mice, suggesting a potentially causal role of bacteria (37)(38)(39).…”
Section: The Gastrointestinal Microbiota and The Immune Systemmentioning
confidence: 99%
“…These effects could be reversed by the addition of the missing enzyme to food. Such animal models suggest that the ability of microbial products to traverse the gut barrier -perhaps to the immune surveillance of the gutassociated lymphoid tissue, may be a key determinant of the development of obesity and metabolic issues (36,43).…”
Section: The Gastrointestinal Microbiota and The Immune Systemmentioning
confidence: 99%